(untitled) (Research, Society and Development, 2022)
The health system overload on a global scale was one of the consequences, where elective criteria for urgent and emergency surgeries were adapted to a new reality. In the case of aortic stenosis surgery (AS), the transcatheter aortic valve replacement (TAVR) technique was prioritized over conventional surgery (AVR) for being less invasive and indicated for patients at risk. To assess the feasibility of the study, we conducted a previous search where individual searches were made in PubMed, Scielo, and Web of Science, using Mesh/Decs descriptors and Boolean operators, where 129 articles were found and 10 were selected. We found that the screening of TAVR occurred mainly by analyzing the severity of symptoms of AS, reduced left ventricular ejection fraction, history of stroke, obstructive coronary disease, associated with the risk of infection. Surgical intervention through TAVR was shown to be safe in patients with high cardiovascular risk, regardless of the risk of sars-cov-2 infection. We conclude that TAVR is recommended in a pandemic scenario, mainly for reducing thromboembolic complications and even with risk of contamination, surgery should be performed to avoid possible deaths.